The internalization signal in the cytoplasmic tail of lysosomal acid phosphatase consists of the hexapeptide PGYRHV. - Lehmann, L E (1992)
Lysosomal acid phosphatase (LAP) is rapidly internalized from the cell surface due to a tyrosine-containing internalization signal in its 19 amino acid cytoplasmic tail. Measuring the internalization of a series of LAP cytoplasmic tail truncation and substitution mutants revealed that the N-terminal 12 amino acids of the cytoplasmic tail are sufficient for rapid endocytosis and that the hexapeptide 411-PGYRHV-416 is the tyrosine-containing internalization signal. Truncation and substitution mutants of amino acid residues following Val416 can prevent internalization even though these residues do not belong to the internalization signal. It was shown recently that part of the LAP cytoplasmic tail peptide corresponding to 410-PPGY-413 forms a well-ordered beta turn structure in solution. Two-dimensional NMR spectroscopy of two modified LAP tail peptides, in which the single tyrosine was substituted either by phenylalanine or by alanine, revealed that the tendency to form a beta turn is reduced by 25% in the phenylalanine-containing peptide and by approximately 50% in the alanine-containing mutant peptide. Our results suggest, that in the short cytoplasmic tail of LAP tyrosine is required for stabilization of the right turn and that the aromatic ring system of the tyrosine residue is a contact point to the putative cytoplasmic receptor.